2008
DOI: 10.1007/s10562-008-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

A CO-Tolerant Hydrogen Fuel Cell System Designed by Combining with an Extremely Active Pt/CNT Catalyst

Abstract: Complete oxidation of 2,000 ppm CO in H 2 is attained over 10 wt.% Pt/CNT (carbon nano-tube) catalyst (0.019 g) at room temperature by adding 2,000 ppm O 2 to hydrogen flowing at 100 mL/min. By insetting 5 wt.% Pt/ CNT catalyst (0.8 g) in front of a PEFC (polymer electrolyte hydrogen fuel cell), the PEFC generated maximum wattage of 0.45 V 9 0.75 A/cm 2 with no suppression for more than 7 h in a flow of H 2 (400 mL/min) containing 1,000 ppm CO. This result suggests a possibility of the hydrogen fuel cell opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, several obstacles exist, while pursuing application of this technology in a large scale. Compared to the oxidation of hydrogen at anode, oxygen reduction reaction (ORR) at cathode is more sluggish with complicated reaction pathways, leading to high overpotential even on Pt catalyst [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For this reason, large amount of Pt as a carbon-supported form are usually used as the cathode catalyst for the production of desired level of power.…”
Section: Introductionmentioning
confidence: 99%
“…However, several obstacles exist, while pursuing application of this technology in a large scale. Compared to the oxidation of hydrogen at anode, oxygen reduction reaction (ORR) at cathode is more sluggish with complicated reaction pathways, leading to high overpotential even on Pt catalyst [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For this reason, large amount of Pt as a carbon-supported form are usually used as the cathode catalyst for the production of desired level of power.…”
Section: Introductionmentioning
confidence: 99%
“…It was first confirmed that 5 wt % Pt/CNT catalyst (∼0.8 g) installed in front of the humidifier of the PEFC worked well as the catalyst for the PROX of CO in H 2 . As shown in Figure a, no decline of the out-put voltage at 0.75 A/cm 2 occurred for more than 7 h in a flow of H 2 (400 mL/min) containing 1000 ppm of CO and 25 000 ppm O 2 ; that is, 1000 ppm CO in H 2 was completely oxidized on the 5 wt % Pt/CNT catalyst (∼0.8 g) installed in front of the humidifier . In contrast, when a Pt/CNT catalyst was installed by contacting with the anode, the out-put voltage of the PEFC was dropped quickly when 500 ppm CO was added to H 2 as shown in Figure b.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 10a, no decline of the out-put voltage at 0.75 A/cm 2 occurred for more than 7 h in a flow of H 2 (400 mL/min) containing 1000 ppm of CO and 25 000 ppm O 2 ; that is, 1000 ppm CO in H 2 was completely oxidized on the 5 wt % Pt/CNT catalyst (∼0.8 g) installed in front of the humidifier. 20 In contrast, when a Pt/CNT catalyst was installed by contacting with the anode, the out-put voltage of the PEFC was dropped quickly when 500 ppm CO was added to H 2 as shown in Figure 10b. This fact indicates that the Pt/CNT catalyst is deactivated by contacting with the anode, and the oxidation of CO was prohibited.…”
Section: Resultsmentioning
confidence: 99%
“…Heat-treated metal-porphyrin, in which metal ions such as Co and Fe are bound to nitrogen in carbon structure, has been proposed as an effective alternative cathode catalyst [5][6][7]. Although the materials may be abundant in nature and consequently can be supplied at lower price, their catalytic activity and stability are currently insufficient for the cathode catalyst utilization.…”
Section: Introductionmentioning
confidence: 99%